2022
DOI: 10.1021/acs.est.2c04107
|View full text |Cite
|
Sign up to set email alerts
|

Plasma PFOA and PFOS Levels, DNA Methylation, and Blood Lipid Levels: A Pilot Study

Abstract: Exposure to perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) is associated with blood lipids in adults, but the underlying mechanisms remain unclear. This pilot study aimed to investigate the associations between PFOA or PFOS and epigenome-wide DNA methylation and assess the mediating effect of DNA methylation on the PFOA/PFOS-blood lipid association. We measured plasma PFOA/PFOS and leukocyte DNA methylation in 98 patients enrolled from the hospital between October 2018 and August 2019. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…From October 2018 to August 2019, 114 adult volunteers were recruited from Shiyan Renmin Hospital in Hubei Province [ 24 ]. They had elective surgery for benign or cosmetic plastic surgery needs, WBC count less than 10 × 10 9 /L, and no serious systemic diseases such as malignancy, autoimmune diseases, heart or kidney failure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From October 2018 to August 2019, 114 adult volunteers were recruited from Shiyan Renmin Hospital in Hubei Province [ 24 ]. They had elective surgery for benign or cosmetic plastic surgery needs, WBC count less than 10 × 10 9 /L, and no serious systemic diseases such as malignancy, autoimmune diseases, heart or kidney failure.…”
Section: Methodsmentioning
confidence: 99%
“…The epigenome-wide DNA methylation levels were measured using Illumina Human MethylationEPIC BeadChip 850K (Illumina Inc, USA). Raw methylation IDAT files were processed using the “minfi” package and “wateRmelon” in R. The detail of the QC process has been described in our previous study [ 24 ]. We normalized the data using the “preprocessNoob” function [ 25 ] and the “BMIQ” function [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…§Increased risk of dyslipidemia was defined as ≥2.3 mmol/L for TG (high TG), or ≥6.2 mmol/L for TC (high TC), or ≥4.1 mmol/L for LDL-C (high LDL-C), or <1.0 mmol/L for HDL-C (low HDL-C). PFNA, PFDA, and PFOS being associated with higher total serum cholesterol and LDL-C. 62,87,111 However, these studies reported disparate results for the associations between PFAS and HDL-C (null results or decreased HDL-C) and PFAS and triglycerides (null results or increasing triglycerides). 62,87,111 Analysis of participants in the Isomers of C8 Project (China, 1238 participants) showed that both PFOA and PFOS were associated with total serum cholesterol and LDL-C but not HDL-C or triglycerides.…”
Section: Dyslipidemia and Atherosclerosismentioning
confidence: 99%
“…PFNA, PFDA, and PFOS being associated with higher total serum cholesterol and LDL-C. 62,87,111 However, these studies reported disparate results for the associations between PFAS and HDL-C (null results or decreased HDL-C) and PFAS and triglycerides (null results or increasing triglycerides). 62,87,111 Analysis of participants in the Isomers of C8 Project (China, 1238 participants) showed that both PFOA and PFOS were associated with total serum cholesterol and LDL-C but not HDL-C or triglycerides. 112 Cross-sectional analysis of a contaminated community in Laizhou Bay, China (162 participants), showed that PFOA (the predominant PFAS) was linked with total serum cholesterol and LDL-C but not HDL-C or triglycerides.…”
Section: Dyslipidemia and Atherosclerosismentioning
confidence: 99%
“…Prolonged exposure to air pollutants or other environmental chemicals, such as PFAS, are associated with altered lipid profile and energy metabolism in both animal and human models, increasing the risk of cardiovascular issues in the exposed population [12] , [13] , [14] , [15] . PFOA and PFOS have been suggested to exert hyperlipidemic effects through the activation of PPARα in animal models, however other mechanisms have been suggested, including the alteration of oxidative stress-related pathways and the modification of the DNA methylation pattern [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%